2010
DOI: 10.1016/j.pec.2010.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Do antidepressant advertisements educate consumers and promote communication between patients with depression and their physicians?

Abstract: Objective-To examine how online depression support group members respond to direct-toconsumer (DTC) antidepressant advertising.Methods-Survey of 148 depression forum members, administered via an online questionnaire.Results-Chronicity was high, as 79.1% had received a diagnosis of depression 3 or more years earlier. Respondents reported seeing advertisements for an average of 4.3 of 7 brands investigated. A majority rated the information quality of these advertisements as "poor" or "fair." Attitudes toward ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…A Kaiser Foundation and Harvard School of Public Health survey concluded that onethird (32%) of Americans had talked to their physician about an advertised medication (Kaiser Family Foundation, 2008). However, others have reported lower rates of requests, from 13% (Bell et al, 2010;Deshpande et al, 2004) to 10% or less Parnes et al, 2009).…”
Section: -2012mentioning
confidence: 94%
See 2 more Smart Citations
“…A Kaiser Foundation and Harvard School of Public Health survey concluded that onethird (32%) of Americans had talked to their physician about an advertised medication (Kaiser Family Foundation, 2008). However, others have reported lower rates of requests, from 13% (Bell et al, 2010;Deshpande et al, 2004) to 10% or less Parnes et al, 2009).…”
Section: -2012mentioning
confidence: 94%
“…Patient reports of whether they discussed or requested a particular medication that they saw advertised continued to vary. Such conversations increased slightly and ranged from 39.9% to 42% (Bell, Taylor, & Kravitz, 2010;Deshpande, Menon, Perri, & Zinkhan, 2004). A Kaiser Foundation and Harvard School of Public Health survey concluded that onethird (32%) of Americans had talked to their physician about an advertised medication (Kaiser Family Foundation, 2008).…”
Section: -2012mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, health and policy scholars have devoted increased attention to online medication sites in order to understand how they may affect people's health-related beliefs and behaviors (e.g., Bell, Taylor & Kravitz, 2010;Calfee, 2007;Donohue & Berndt, 2004;Kim & Seong, 2010). Within this program of research, a growing number of empirical studies have found direct-to-consumer advertisement (DTCA) sites may have class-wide effects, meaning that advertisements for prescription medications can increase demand for the advertised drug as well as the demand for related medications (Atherly & Rubin, 2009;Rosenthal, Berndt, Donohue, Epstein, & Frank, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of DTC advertisements have been documented in numerous academic and industry studies, which routinely find positive associations between exposure to DTC advertisements and outcomes such as patientdoctor dialogue (e.g., Bell et al, 2010;Choi & Lee, 2007) increased prospect conversion (Aquino, 2011) and patient refills (Bradley & Zito, 1997). While only a small subset of DTCA researchers has focused specifically on psychiatric treatments, studies examining the effects of DTC advertisements for antidepressant medications have yielded similarly promising findings (e.g., Soontae, Hyun Seung, & Brown, 2009;Donohue & Berndt, 2004).…”
Section: Introductionmentioning
confidence: 99%